Effects of 1,8-cineole on Carbohydrate Metabolism Related Cell Structure Changes of Salmonella - Sun, Yangying; Cai, Xiaojun; Cao, Jinxuan; Wu, Zhen; Pan, Daodong (Frontiers in Microbiology, 2018)
Salmonella is gram-negative foodborne zoonotic bacteria which triggers disease in humans. Our previous studies showed 1,8-cineole possessed remarkable antimicrobial effects on foodborne zoonotic bacteria indicating it could serve as a new source of antibiotic for Salmonella. Present study elucidated the antibacterial mechanism of 1,8-cineole by analyzing serum protein expressed by Salmonella following treatment with 1,8-cineole (0.25 mg/mL, 3 h) using isobaric tags for relative and absolute quantification (iTRAQ) with two-dimensional liquid chromatography/tandem mass spectrometry (2D-LC-MS/MS). 1,8-cineole was found to significantly damage the structure of Salmonella cell walls and membranes. A total of 3011 proteins were extracted from the experimental group, of which 435 were differentially expressed (1.5 fold) with 123 upregulated and 312 downregulated. The expressed proteins were involved in 935 intracellular biological processes, 98 cellular components, 477 molecular functions and 86 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Among them, proteins associated with carbohydrate, nucleotide, amino acid, lipid and energy metabolism were significantly changed following treatment with 1,8-cineole. Carbohydrate metabolism and membrane protein-related genes was down-regulated at the mRNA level when Salmonella was treated with 1,8-cineole. 1,8-cineole may be a potential antibiotic for Salmonella infections.